Longitudinal study of normal cognition in Parkinson disease. (13th October 2015) - Pigott, Kara; Rick, Jacqueline; Xie, Sharon X.; Hurtig, Howard; Chen-Plotkin, Alice; Duda, John E.; Morley, James F.; Chahine, Lama M.; Dahodwala, Nabila; Akhtar, Rizwan S.; Siderowf, Andrew; Trojanowski, John Q.; et al.
Abstract : Objective: To report the rates and predictors of progression from normal cognition to either mild cognitive impairment (MCI) or dementia using standardized neuropsychological methods. Methods: A prospective cohort of patients diagnosed with Parkinson disease (PD) and baseline normal cognition was assessed for cognitive decline, performance, and function for a minimum of 2 years, and up to 6. A panel of movement disorders experts classified patients as having normal cognition, MCI, or dementia, with 55/68 (80.9%) of eligible patients seen at year 6. Kaplan-Meier curves and Cox proportional hazard models were used to examine cognitive decline and its predictors. Results: We enrolled 141 patients, who averaged 68.8 years of age, 63% men, who had PD on average for 5 years. The cumulative incidence of cognitive impairment was 8.5% at year 1, increasing to 47.4% by year 6. All incident MCI cases had progressed to dementia by year 5. In a multivariate analysis, predictors of future decline were male sex ( p = 0.02), higher Unified Parkinson's Disease Rating Scale motor score ( p ⩽ 0.001), and worse global cognitive score ( p < 0.001). Conclusions: Approximately half of patients with PD with normal cognition at baseline develop cognitive impairment within 6 years and all new MCI cases progress to dementia within 5 years. Our results show that the transition from normal cognition to cognitive impairment, including dementia, occurs frequently and quickly. Certain clinical and cognitive variables may be useful in predicting progression to cognitive impairment in PD.